Pendidikan Islam Perspektif Mohammad Natsir Dan Hasan Langgulung - Sofia Murni (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2024)
This journal aims to obtain a description of Islamic education in the perspective of Mohammad Natsir and Hasan Langgulung. The subject of this journal focuses on the thought of Muhammad Natsir and Education at that time tended to secular and dichotomised education systems, far from the touch of spiritualization. In addressing this problem it is necessary to bring in the Muslim figures who struggle in Islamic education among them Mohammad Natsir and Hasan Langgulung. This research uses a library method. (Library Reseahch). The data collected is then reinterpreted using descriptive analysis methods. In this article, the concept of Islamic education according to Mohammad Natsir and Hasan Langgulung is focused on four elements, namely on the purpose of education, educational material, methods of education and educators. It is the creation of a righteous man who believes in Allah and His Messenger, and the formation of a good people who follow the guidance of Islam in all their affairs.